Soft-sediment deformation structures of tide origin: A case study from the late Miocene Tafna Basin (NW Algeria) - Benzina, Mostapha; Draoui, Abdelmalik; Hebib, Hakim; Pisarska-Jamroży, Małgorzata (Proceedings of the Geologists' Association, 2025)
Typical liquefaction-induced soft-sediment deformation structures were recognised in the Neogene-age tide-dominated estuarine sedimentary succession Bled El Trayfa in the Tafna basin (NW Algeria). Although NW Algeria was tectonically active during late Neogene, we suggest that another trigger mechanism that is not related to earthquakes is responsible for the liquefaction phenomenon and the development of soft-sediment deformation structures in the area. The sedimentary succession called the Bled El Trayfa exhibits tidal rhythmites, heterolithic beddings, bi-directional cross-laminae, and tidal bore couplets deposited in tidal flats within the intertidal environment. A tidal bore, defined as upstream-propagating hydraulic jumps associated with the flood tide in estuarine rivers, is proposed as the main trigger mechanism responsible for the liquefaction phenomenon and the development of soft-sediment deformation structures. This suggestion was made on a set of observed arguments: firstly, the presence of draping massive sand underlain by erosional surfaces indicating scouring by upstream-propagating bores, followed by a very rapid deposition in a tide-dominated estuarine from the intertidal environment and secondly, the formation of distinctive (typical) soft-sediment deformation structures, characterised by convoluted and folded structure like flow rolls along with associated dewatering structures. Alongside flow rolls as typical and dominant soft-sediment deformation structures, the succession also includes load casts, recumbent folds, water-escape structures, convolute laminations, ball-and-pillow structures, and flame structures. Even though the relationship between the tidal bore and sediment deformation structures has been proved in some current researches, the Bled El Trayfa succession was considered among the rare areas where this relationship was identified as the origin of SSDSs in ancient rock record.